A counterexample in the theory of linear singularly perturbed systems (1991)
In this note we compare the bounded solutions of the linear singularly perturbed system ε X' = A (t) x + f (t), with the solutions of the algebraic system A (t) x + f (t) = 0.  Here A and  f  are bounded C1 functions with bounded derivatives. We assume that the eigenvalues of A (t) satisfy | R e λ (t )| ≥ y and gt; 0. It is known that for small ε, the following estimate is valid hasta ||kε (f) + A-1 f || ≤  εL || f ||1, where kε(f) denotes the bounded solution of ε X'  = A(t)x +f (t), || f || = sup R| f(t)|, || f ||1 : = || f || +|| f´ ||  and L is a constant. We prove that this estimate cannot be replaced by ||kε (f) + A-1 f || ≤  εL || f ||. Futhermore, if, instead of the condition that A be C1, we require that the function be bounded and Lipschitz continuous, we show that the same estimate, ||kε (f) + A-1 || ≤  εL || f ||1, can be obtained.